2016
DOI: 10.1159/000442824
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Trauma-Focused Cognitive Behavioral Therapy for Children and Adolescents: A Randomized Controlled Trial in Eight German Mental Health Clinics

Abstract: Background: Trauma-focused cognitive behavioral therapy (Tf-CBT) is efficacious for children and adolescents with posttraumatic stress symptoms (PTSS). Its effectiveness in clinical practice has still to be investigated. Aims: To determine whether Tf-CBT is superior to waiting list (WL), and to investigate the predictors of treatment response. Method: We conducted a single-blind parallel-group randomized controlled trial in eight German outpatient clinics with the main inclusion criteria of age 7-17 years, sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
110
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 28 publications
13
110
1
2
Order By: Relevance
“…Youth in the WL arm experienced some nontrivial recovery (33% experienced clinically significant change), at a level broadly comparable with other WL‐controlled RCTs (Goldbeck, Muche, Sachser, Tutus, & Rosner, ; King et al., ; Smith et al., ). Nevertheless, this RCT suggests that youth identified as having PTSD in the 2‐ to 6‐months window post‐trauma are more likely than not to require treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Youth in the WL arm experienced some nontrivial recovery (33% experienced clinically significant change), at a level broadly comparable with other WL‐controlled RCTs (Goldbeck, Muche, Sachser, Tutus, & Rosner, ; King et al., ; Smith et al., ). Nevertheless, this RCT suggests that youth identified as having PTSD in the 2‐ to 6‐months window post‐trauma are more likely than not to require treatment.…”
Section: Discussionsupporting
confidence: 71%
“…TF-CBT is not only associated with a significant reduction of posttraumatic stress symptoms (PTSS), depressive and anxiety symptoms, behavioral problems, and dysfunctional trauma-related cognitions, but also with improvement of psychosocial functioning [2,3]. …”
Section: Tablementioning
confidence: 99%
“…So far, only one study has demonstrated the long-term effectiveness of TF-CBT in real-world clinical settings, with youth who had been exposed to different traumatic events [5]. As this study used only self-report questionnaires, we aimed to further evaluate the long-term effectiveness of TF-CBT within our recent multicenter randomized controlled trial (RCT) [2], using multiple informants. Our hypothesis was that all improvements regarding PTSS, remission of PTSD diagnoses, psychosocial functioning, trauma-related cognitions, depression, anxiety, other internalizing and externalizing symptoms, and quality of life (QoL) at posttreatment would be maintained at 6- and 12-month follow-ups (6MFU, 12MFU).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations